Increased Plasma Heparanase Activity and Endothelial Glycocalyx Degradation in Dengue Patients Is Associated With Plasma Leakage - Buijsers, Baranca; Garishah, Fadel Muhammad; Riswari, Silvita Fitri; van Ast, Rosalie M.; Pramudo, Setyo Gundi; Tunjungputri, Rahajeng N.; Overheul, Gijs J.; van Rij, Ronald P.; van der Ven, André; Alisjahbana, Bachti; Gasem, Muhammad Hussein; de Mast, Quirijn; et al. (Frontiers in Immunology, 2021)
Background Endothelial hyper-permeability with plasma leakage and thrombocytopenia are predominant features of severe dengue virus infection. It is well established that heparanase, the endothelial glycocalyx degrading enzyme, plays a major role in various diseases with vascular leakage. It is yet to be elucidated whether heparanase activity plays a major role in dengue-associated plasma leakage. Moreover, the major source of heparanase secretion and activation in dengue remains elusive. Since a relatively high amount of heparanase is stored in platelets, we postulate that heparanase released by activated platelets contributes to the increased plasma heparanase activity during dengue virus infection. Methods Heparanase activity (plasma and urine), and heparan sulfate and syndecan-1 (plasma levels) were measured in dengue patients with thrombocytopenia in acute phase (n=30), during course of disease (n=10) and in convalescent phase (n=25). Associations with clinical parameters and plasma leakage markers were explored. Platelets from healthy donors were stimulated with dengue non-structural protein-1, DENV2 virus and thrombin to evaluate heparanase release and activity ex vivo. Results Heparanase activity was elevated in acute dengue and normalized during convalescence. Similarly, glycocalyx components, such as heparan sulfate and syndecan-1, were increased in acute dengue and restored during convalescence. Increased heparanase activity correlated with the endothelial dysfunction markers heparan sulfate and syndecan-1, as well as clinical markers of plasma leakage such as ascites, hematocrit concentration and gall-bladder wall thickening. Notably, platelet number inversely correlated with heparanase activity. Ex vivo incubation of platelets with thrombin and live DENV2 virus, but not dengue virus-2-derived non-structural protein 1 induced heparanase release from platelets. Conclusion Taken together, our findings suggest that the increase of heparanase activity in dengue patients is associated with endothelial glycocalyx degradation and plasma leakage. Furthermore, thrombin or DENV2 activated platelets may be considered as a potential source of heparanase.